Hypothesizing the Mechanism of Action of Virechana in Neurological Diseases with Respect to the Gut-Brain Microbiota Axis (AYUSHDHARA, 2025)
Panchakarma is an efficient and popular Ayurvedic treatment modality that helps eliminate various Doshic imbalances in the body to prevent and treat diseases. Its efficacy is being proven through multiple studies conducted across the globe; still, the mode of action of these therapies is to be understood far and wide. Virechana is one of the Panchakarmas that have an impact on the whole body to remove the Doshas that spread across the entire system. Due to this reason, it is considered best in the management of many disorders affecting different systems of the body, including the nervous system. The present review aimed at understanding the mechanism of action of Virechana with respect to the microbiota-gut-brain axis in neurological diseases. Virechana using Mridu and Snigdha medicines is mentioned for the management of Vatarogas. As Virechana is considered the primary treatment of pitta, its effect may be related to hormones and enzymes having neuroregulatory properties also. The microbiota-gut-brain axis plays an active role in the pathogenesis, management, and prevention of neurological diseases. Gastrointestinal complications like constipation are common in diseases affecting the nervous system, and they have shown a negative correlation with neurological recovery. Here comes the importance of Snigdha virechana or Mridu virechana mentioned in Vatavyadhi. Virechana can remove unfavorable bacterial colonization and is effective in correcting gut flora dysbiosis. Thus, the mechanism of action of Virechana in modifying the gut-brain axis and thereby facilitating neurologic recovery is understood.  The present review sheds light on the Mechanism of action of Virechana with respect to the microbiota gut-brain axis in neurological disorders, which may be helpful for further research.